Early European accounting theory: Sir William Petty's contributions to accounting. (1st January 2014) - Sy, Aida; Tinker, Tony
Accounting and auditing are frequently cited as culprits in the current economic crisis. Traditional practices (including academic rationales) are coming under increased scrutiny. This paper proposes a way of beginning to reinvigorate the subject by returning to the classics. Accounting, as a social science has several origins. This paper explores these diverse origins of accounting starting with the work of one of the 'Fathers of Accounting', Sir William Petty, the first general comptroller of England. Petty lived during the 17th century and published a variety of works on political economy that extended into accounting of the period.